Saccade dysmetria in Williams–Beuren syndrome - van der Geest, J.N.; Lagers-van Haselen, G.C.; van Hagen, J.M.; Govaerts, L.C.P.; de Coo, I.F.M.; de Zeeuw, C.I.; Frens, M.A. (Neuropsychologia, 2004)
Numerous studies have described the poor visuo-spatial processing capacities of subjects with Williams–Beuren syndrome (WBS), a genetically based developmental disorder. Since visual perception and eye movements are closely related we hypothesized that the poor visuo-spatial processing capacities of subjects with WBS might be related to a poor saccadic control. Thereto, we recorded horizontal and vertical saccadic eye movements to targets using infrared video-oculography in 27 subjects with WBS and eight healthy controls. In the WBS group saccadic gains were highly variable, both between and within individual subjects, and they often needed more than one correction saccade to reach the target. Ten (out of a subgroup of 22) WBS subjects showed a large number of hypometric and/or hypermetric saccades, and, also a left–right asymmetry in saccadic gains was observed in WBS. We conclude that the observed impairments in saccadic control are likely to affect the proper processing of visuo-spatial information.